2007
DOI: 10.1093/beheco/arm067
|View full text |Cite
|
Sign up to set email alerts
|

Sexual conflict over copula timing: a mathematical model and a test in the yellow dung fly

Abstract: Sexual conflict over mating occurrence, timing, or duration is common in animals. This explains conspicuous female mate rejection behavior in many species, often involving shaking, fighting, and occasional forced copulations. We present a simple model that generates predictions about whether and when copulation occurs in such conflict situations and how much female rejection behavior should be observed. Predictions depend on 2 underlying parameters affecting female resistance and male persistence. We supply 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
(80 reference statements)
2
6
0
Order By: Relevance
“…Previous work in S. stercoraria is consistent with this pattern, finding greater female resistance in non-gravid females, although reports of resistance have described the behaviour as gentle shaking or swaying and suggested that it probably does not function in mate choice [59,60]. In striking contrast to these earlier reports, we observed vigorous resistance, predominantly exhibited by non-gravid females, and provide evidence that such behaviour is nonrandomly directed such that females discriminate against large males.…”
Section: Discussionsupporting
confidence: 82%
“…Previous work in S. stercoraria is consistent with this pattern, finding greater female resistance in non-gravid females, although reports of resistance have described the behaviour as gentle shaking or swaying and suggested that it probably does not function in mate choice [59,60]. In striking contrast to these earlier reports, we observed vigorous resistance, predominantly exhibited by non-gravid females, and provide evidence that such behaviour is nonrandomly directed such that females discriminate against large males.…”
Section: Discussionsupporting
confidence: 82%
“…Selection pressures on age and size at maturity differ between males and females (Leimar 1996, Tammaru 1998). Indeed, large size is generally highly advantageous for females due to its strong relationship with increased fecundity (Tammaru et al 2002, Parry et al 2001), whereas rapid development is more important for males in terms of increasing mating success (Blanckenhorn et al 2007). However, selection pressures on larvae are not sex‐based (Esperk et al 2007b), and size optima are presumably the same for both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Selection should favour unreceptivity to mating unless the advantages of receptivity outweigh the costs of mating. Females can and do reject copulations: copulations with nongravid females away from dung [13,21] and with females immediately after they have completed oviposition at the dropping [5] are both shortened by the violent side-to-side shaking movements of unreceptive females. However, unreceptivity would subject an ovipositing female to repeated harassment by searching males if not guarded by the last male to mate.…”
Section: The Adaptive Significance Of Female Receptivitymentioning
confidence: 99%